The Legal Standing of PPKM in Banten Province (Constitutional Law Perspective - Eki Furqon; Qotrun Nida (Nurani Hukum, 2022)
The establishment of the policy for the Implementation of Restrictions on Community Activities (PPKM) is one of the efforts to overcome the pandemic carried out by the Indonesian government. The legal basis for the PPKM policy is contained in the Instruction of the Minister of Home Affairs, which is a problem because of the pandemic situation which is a national disaster but the policies used are only regulated in the minister's instructions. Banten Province, which is included in the Java-Bali PPKM area imposed by the central government, has issued a policy containing the implementation of PPKM as stipulated in the Banten Governor's Instruction Number 1 of 2021. These problems then have an impact on the extent of the binding power of the PPKM when viewed from the legal basis, its formation is related to the hierarchical system of legislation in Indonesia. The research method used is a normative juridical research method with the aim of seeing how the normative arrangements regarding the legal position of PPKM in Banten Province are in the Indonesian constitutional system. Using secondary data such as literature and literature but also using primary data or field data as supporting data. The policy in the form of a ministry instruction in this case the Instruction of the Minister of Home Affairs regarding PPKM cannot be used to regulate matters that are comprehensive or external to the ministry itself. Therefore, the use of a Ministerial Instruction in handling Covid-19 is not appropriate because it is not a legal product in the form of a regulation that can bind all parties and have clear legal consequences.